Neutron Scattering Study of Chain Conformations in the Energetically Neutral Pores of Vycor Glass - Nieh, Mu-Ping; Ho, Derek L; Briber, Robert M (Macromolecules, 2002)
Small-angle neutron scattering is used to study the conformation of polymer chains of various lengths, N ∼ 1200−7000, in good solvent confined to the energetically neutral pores of a model Vycor glass with a mean pore diameter of D = 70 Å. This study utilized an external polymer concentration, c free, well into the overlapped or semidilute regime. Analysis of the experimental data using the standard bulk analysis procedure yields the surprising result that the chain dimensions in the pore are the same as in the unconfined solution. Since simulation results for comparable physical situations, which suggest that chains expand when they are strongly confined, are not in agreement with this interpretation, we conclude that our analysis misses some aspect of the experimental situations. To reconcile this discrepancy between theory and experimental results, we utilize the facts that the chains are strongly confined in one direction by the pore walls and that the pores are themselves random walks rather than straight cylindrical objects. A reanalysis of the experimental data on this basis then shows that chain dimensions in the pores are swollen relative to an unconfined chain, in a manner that is in agreement with the recent simulations of van Giessen and Szleifer. While these results provide the first quantitative tests of these simulation results, we nevertheless conclude that the random nature of the pore geometry in Vycor makes the conclusions drawn very subject to the particular models employed in the analysis of experimental data.